Implementation of Character Education at Madrasah Ibtidaiyah Luqman Al Hakim Slawi and Budi Mulia Muhammadiyah Adiwerna Elementary School - Santoso, Budi; Suriswo, Suriswo; Nugraha, Rahmad Agung (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to describe the implementation of character education at Madrasah Ibtidaiyah Luqman Al Hakim Slawi and Budi Mulia Muhammadiyah Elementary School Adiwerna. Character education is a crucial aspect in shaping students' personality and moral values from an early age. This research employs a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and documentation. The research subjects include school principals, teachers, students, and parents. The findings reveal that the implementation of character education in both institutions is carried out through three main pathways: intraclass activities, co-curricular, and extracurricular programs. The character values developed include religiosity, discipline, responsibility, honesty, care, and cooperation. At MI Luqman Al Hakim Slawi, an integrative approach is applied by internalizing character values within Integrated Islamic-based learning. Meanwhile, at Budi Mulia Muhammadiyah Elementary School Adiwerna, the approach focuses on strengthening school culture and flagship programs rooted in Muhammadiyah values. Supporting factors in implementation include the schools’ vision and mission, educators’ commitment, and parental involvement. Challenges encountered involve students' diverse backgrounds and limited time for implementing character programs. This study recommends the importance of continuous collaboration among schools, parents, and communities to strengthen holistic character education.